Towards carbon neutrality: Improving resource efficiency of the rare earth elements in China - Ge, Zewen; Geng, Yong; Dong, Fanli; Liang, Jingjing; Zhong, Chen (Frontiers in Environmental Science, 2022)
Rare earth elements (REEs) are essential for promoting clean energy technologies and making high-performance materials because of their unique physical and chemical properties. In order to respond to climate change, the Chinese government has promised to achieve carbon neutrality before 2060. Under such a circumstance, the demand for REEs will increase significantly. However, several challenges exist in current REEs supply chain management in China. This policy brief discusses these challenges from a life cycle perspective, covering REEs mining, smelting, manufacturing, waste management, and recycling. Policy recommendations on future REEs supply chain management are then proposed, including adequate mining quota, a strategic REEs list, innovative high-tech applications, and circular economy.